A stress gradient approach for fretting fatigue assessment of metallic structural components. (August 2017) - Vantadori, Sabrina; Fortese, Giovanni; Ronchei, Camilla; Scorza, Daniela
Highlights: Fretting fatigue life of metallic components under cylindrical contacts is evaluated. A critical plane-based multiaxial high-cycle fatigue criterion is applied. Fatigue life is assessed at a certain distance from the contact surface. Such a distance regarded as a material property is measured along alternative paths. Finally a distance depending on the stress gradient in the contact zone is proposed. Abstract: In the present paper, the fretting fatigue life assessment of metallic structural components under cylindrical contacts is performed by applying a critical plane-based multiaxial fatigue criterion. Such a criterion is formulated by using the so-called critical point method: a material point located at a certain distance from the hot-spot on the contact surface is assumed to be the critical point where to perform the above assessment. The above distance, function of the material properties, is measured along three alternative paths (a normal path, an inclined path and a principal stress oriented path) and, using such three different paths to determine the critical point location, the effectiveness of the criterion is evaluated by means of experimental data related to aluminium alloy specimens under cylindrical contacts. Further, in order to improve the accuracy of the critical plane-based criterion in terms of fretting fatigue lifetime evaluation, a new approach involving a critical distance also function of the stress gradient in the contact zone is proposed and experimentally validated.